Straightforward preparation of nickel selenide nanosheets supported on nickel foam as a highly efficient electrocatalyst for oxygen evolution reaction. (19th July 2022) - Wang, Yuqing; He, Fangzhen; Ren, Yanmei; Lin, Yasu; Zhong, Ming; Su, Bitao; Lei, Ziqiang
Abstract: The development of economical, durable, and efficient oxygen evolution reaction (OER) electrocatalysts is essential for large-scale industrial water electrolysis. Here, a straightforward strategy is proposed to synthesize a series of nickel selenide nanosheets supported on nickel foam (NiSe2 /NF) materials by directly selenizing nickel foam substrates at different temperatures under an inert atmosphere. When evaluated as electrocatalysts in OER, the optimal self-supported NiSe2 /NF-350 shows an excellent performance in 1.0 M KOH medium with an overpotential of 458 mV at 100 mA cm −2, a small Tafel slope of 45.8 mV dec −1, and a long-term stability for 36 h. Furthermore, the structural and compositional preservation for NiSe2 /NF-350 after stability test was also verified by various characterizations. Graphical abstract: A quite simple selenization was adopted to prepare self-supported nickel selenide nanosheets/nickel foam materials with excellent OER performance. Image 1 Highlights: NiSe2 /NF was prepared by a super simple selenization. The method has low energy consumption and simple operation. The NiSe2 /NF-350 electrode demonstrates the excellent OER performance.